Virtual reality as a communication tool in the grieving process - Fernández, Manel; Pina, Brenda; Salla García, Xavier (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2019)
In this research work, the authors intend to introduce an approach to the use of virtual reality (VR) technologies, as a tool for the therapeutic treatment of psychological problems and more specifically in the accompaniment of grief. The study is divided into three blocks in which the researchers try to frame the current conception of the term virtual reality, the concept of non-pathological grief and how today's society faces the loss of a loved one and their grieving process. It also addresses how current legislation in the field of data protection, affects the subject of research.